Existing breeding, feeding and housing management practices followed by the milk producers in Guntur district of Andhra Pradesh (Indian Journal of Animal Production and Management, 2017)
A field study was conducted to know the existing breeding, feeding and housing management practices  followed by the landless, small farmer and commercial milk producers in Guntur district of Andhra Pradesh.  Commercial milk producers reared both Murrah and Graded Murrah buffaloes, whereas small farmers and  landless milk producers maintain mostly Graded Murrah buffaloes. Green fodder production was higher  in commercial (100%) and small farmers (97%) than in landless milk producers (13%). Supplementation  of mineral mixture was found to be higher in commercial milk producers (90%) than that in small farmers  (35%) and landless milk producers (16%). All most all landless (99%) category housed their buffaloes in  the open area but only the commercial milk producers were maintaining the sheds (50%) and protect the  animals from adverse climatic conditions. Majority of commercial (86%) and small farmers (27%) arranged  cooling devices like fans in the buffalo sheds.
Keywords: Buffalo breeding; Feeding; Housing; Management practices